KONVERSI AGAMA MIGRAN TORAJA: Motivasi dan Implikasinya terhadap Hubungan Etnik-Religi Toraja di Kota Bontang, Kalimantan Timur - Hudriansyah, Hudriansyah (IAIN Samarinda, 2018)
The aim of this paper is to reveal and understand the motives behind and implications of religious conversion among Torajan Muslim converts from migrant community in the City of Bontang, East Kalimantan Province. Applying qualitative-fenomenological method, this research finds out that the main motives behind religious conversion among Torajan Muslim converts is practical and pragmatic benefits such as to perform marriage. However, the combination of Hidayah (spiritual guidance) from Allah, support from other family members, and influence from social environment are also believed to be other significant reasen behind religious conversion among Torajan Muslim converts in Bontang. Despite facing a number of socio-economic problems, post-conversion politics, and inter-ethnic family disputes resulting from the practice of conversion, family relation among Torajan Christians who convert to Islam and those who remain Cristian are well maintained. In the broader context, religious conversion for practical and pragmatical reasons is not always lead to disruptions in terms of inter-religious relations among migrant community of Torajan people despite the fact that those converts are still marginalized in the area of political economy competition.Keywords: Conversion, muallaf, ethnic-religion, Toraja